Rekonstruksi Pendekatan Heutagogik dalam Perspektif Al-Qur'an dan Hadis Tarbawi serta Implikasinya bagi Pendidikan Islam Kontemporer - Erlani, Erlani; Maya, Rahendra (Dirosah Islamiyah, 2026)
The transformation of education in the era of the Industrial Revolution 4.0 and Society 5.0 requires learning paradigms that foster independence, creativity, critical thinking, adaptability, and lifelong learning. One approach that addresses these demands is heutagogy (self-determined learning), which positions learners as the primary agents in determining their learning goals, strategies, resources, and evaluation. Although heutagogy has been widely studied in higher education and digital learning contexts, most studies are grounded in Western educational perspectives. Meanwhile, Islamic education research generally discusses learning principles derived from the Qur’an and Hadith in a normative manner without integrating them with contemporary learning theories. This gap forms the basis of the present study. This study aims to analyze the concept of the heutagogical approach, examine its foundations from the perspectives of the Qur’an and Tarbawi Hadith, and explore its implications for contemporary Islamic education. The research employs a qualitative method using a library research approach by analyzing literature on heutagogy, Qur’anic verses, Tarbawi hadiths, and relevant scholarly sources.The findings reveal that the core principles of heutagogy are substantially compatible with Islamic educational values. The Qur’anic concepts of tafakkur, tadabbur, ta‘aqqul, and tadzakkur emphasize independent thinking, reflection, and active knowledge seeking. Likewise, the educational methods of the Prophet Muhammad (PBUH), including dialogue, consultation, exemplary conduct, and experiential learning, reflect characteristics consistent with self-determined learning. This study concludes that the heutagogical approach can be reconstructed within the framework of Islamic education through the integration of learner autonomy, moral responsibility, and a tawhid-based spiritual orientation. These findings contribute to the development of an Islamic educational paradigm that is responsive to contemporary challenges while remaining rooted in Islamic values..